Persepsi Mahasiswa Terhadap Implementasi UU PPKSP (Undang-Undang Pencegahan dan Penanganan Kekerasan Seksual di Perguruan Tinggi) - Salsabila, Marisa Jahra; Agatha, Felish; Zakariyya, Muhammad Surya; Aulia, Sri Mutia (INDO PUBLISHING, 2025)
Cases of sexual violence in higher education institutions in Indonesia continue to rise. According to data from the National Commission on Violence Against Women (Komnas Perempuan) in 2024, there were 4,178 cases of violence against women, including in the higher education sector. In response to this issue, the government issued regulations on the prevention and handling of sexual violence in higher education through the Sexual Violence Prevention and Handling Law in Higher Education (UU PPKSP). This study aims to assess the understanding of students at the Universitas Pendidikan Indonesia regarding sexual harassment offenses and their knowledge of the prevention and handling of sexual violence in the context of implementing the UU PPKSP. The research method used is quantitative, with the distribution of questionnaires to students as respondents. The results of the study are expected to provide an overview of the level of understanding and knowledge of students regarding the UU PPKSP, as well as serve as a basis for higher education institutions to strengthen socialization, education, and more effective systems for preventing and addressing sexual violence.